HYDROCHEMISTRY OF SOIL SOLUTION COLLECTED WITH TENSION-FREE LYSIMETERS IN NATIVE AND CUT-AND-BRUNED TROPICAL RAIN FOREST IN CENTRAL AMAZÔNIA - Piccolo, M. C.; Andreux, F.; Cerri, C. C. (Geochimica Brasiliensis, 2011)